Incidence and evolution of the number of bovine tuberculosis cases, in the municipality of Unaí-MG - period 2013-2015 - Ramos, Fernando Silva; Fonseca, Lysandra Martineli; Borges, Leandra Aparecida Leite; Sousa, Joerberson Caixeta de; Almeida, Sabrina Silva (Revista Coleta Científica, 2017)
In this work, an approach is made about bovine tuberculosis and its cause and consequence for affected cattle, the disease is caused by a pathogen, mycobacterium bovis, a bacilliform gram-positive bacterium that lodges in macrophages, and mainly attacks the respiratory system whose frequent clinical signs are: progressive cachexia, short and repeated dry cough, low respiratory capacity and localized or generalized lymphadenomegaly can also occur. Mycobacterium bovis that causes tuberculosis in cattle has great resistance and can live for several months in stables, for example, sheltered from light, the main route of contamination of animals is respiratory, when they inspire aerosols from animals affected by the disease but also through the digestive tract mainly in calves that feed on milk from cows with tuberculous mastitis and animals that ingest contaminated water and forage. With the results obtained, we can see the great relevance of the disease to the region of Unaí-MG, and that its control through the elimination of positive outbreaks is shown to be an effective method against the proliferation of bovine tuberculosis.